One Health Paradigm to Confront Zoonotic Health Threats: A Pakistan Prospective - Yasmeen, Nafeesa; Jabbar, Abdul; Shah, Taif; Fang, Liang-xing; Aslam, Bilal; Naseeb, Iqra; Shakeel, Faiqa; Ahmad, Hafiz Ishfaq; Baloch, Zulqarnain; Liu, Yahong (Frontiers in Microbiology, 2022)
The emergence and re-emergence of zoonotic diseases significantly impact human health, particularly those who live in impoverished areas and have close contact with domestic or wild animals. Nearly 75% of zoonotic diseases are transmitted directly from animals to humans or indirectly via vector/agent interactions between animals and humans. Growing populations, globalization, urbanization and the interaction of the environment with humans and livestock all play roles in the emergence and spread of zoonotic diseases. "One health" is a multidisciplinary concept aimed at improving human, animal, and environmental health but this concept is not widely accepted in developing countries. In Pakistan, environmental, human and animal health are severely affected due to a lack of sufficient resources. This review article provides an overview of the most common zoonotic diseases found in Pakistan and emphasizes the importance of the "One Health" concept in managing these diseases. Given the current situation, interdisciplinary research efforts are required to implement and sustain effective and long-term control measures in animal, human and environmental health surveillance and accurate diagnostic methods.